KEHIDUPAN EKONOMI PETANI GULA MERAH (GULA AREN) DI DESA TONDEI KECAMATAN MOTOLING BARAT KABUPATEN MINAHASA SELATAN - Theresia Angelin Piri (Universitas Sam Ratulangi, 2023)
Indonesia is dubbed as an agricultural country, most people make a living in agriculture, the majority of the population lives in rural areas that depend on the primary sector, especially in agriculture. The agricultural subsector has plant characteristics that can be grouped into two, namely annual crops and annuals. Annual plants are plants that take a long time to produce and can be harvested more than once. Examples such as: rubber, cloves, coconut, palm, and so on. Palm tree (Arengan pinatta Merr) or commonly referred to by local people as seho tree is a plant that is liked by many people because it has many benefits. Many people call this plant a million benefits, the benefits that can be obtained from this seho tree include producing fiber palm, sap for making sugar, and kolang-kaling fruit, as well as brown sugar that has been processed, also has good benefits for health, and can also provide financial benefits for the community's economy. Especially the people of Tondei Village located in West Motoling District, South Minahasa Regency. Most of the people of Tondei are palm farmers, where the people of Tondei Village make palm plants (seho trees) as one of the main livelihoods in improving the economy, especially the use of sap. The people of Tondei Village process palm sap into brown sugar. Keywords: socio-economic, farmer, palm sugar